Using a bradykinin blocker in ACE inhibitor-associated angioedema in the emergency department - Volans, Andrew (BMJ Publishing Group, 2013)
We report two cases of ACE inhibitor-associated angioedema and critical airway compromise, where the use of a selective bradykinin 2 receptor blocker resulted in rapid symptom resolution and prevented intubation to protect the airway.